Pengaruh Berbagai Merek Oli terhadap Temperatur Mesin Honda Scoopy dan Emisi Gas Buang - Firda Herlina; M. Marsudi; Rendi Rendi; Muhamad Syarif (Proklamasi 45 University, 2018)
The development of automotive technology in Indonesia is directly proportional to the use of a lubricant that consumption is also developed from the technology. But from the proposal, we could not confirm whether the factory owners of output oil is better than the oil output in the factories. Of motor vehicle, gas emissions as a source of air pollution reached 60-70 % largest, compared to an industry that is only around 10-15 %. the remembrance of the danger of exhaust gas emissions, business needs to be to control air pollution so that the negative impact of mankind can be minimized. This report is written with the experimental methods, by doing observation experiment every new brand oil and gas emissions. This report is written with the experimental methods are, with supervising the case spread experiment luminance to the change of a brand oil and test it of gas emission of the exhaust. The results of this honda motor vehicle Scoopy 2013 is better to use the oil the list of top 1 oil because having the value of the wide range of temperatures 64.6 oC. Honda motor vehicle scoopy 2015 is better to use the Ahm Mpx2 oil because having the value of the wide range of temperatures 73.6 oC Honda motor vehicle scoopy 2017 is better to use the Top 1 oil because having the value of the wide range of temperatures 66.7 oC. Condition and exhaust gas emissions could be lowered in concluded that honda Scoopy 2013 with Top 1 oil is about CO which better for that which is 0.96 while for the program the nature of all that HC and CO2 that is good uses Ahm Mpx2 oil. Honda Scoopy 2015 with Ahm Mpx2 oil is about CO, HC, and CO2 who good and stable. Honda Scoopy 2017 with Top 1 oil is about CO which better for that which is 0.81 while for the program the nature of all that HC that is good uses Ahm Mpx2 oil and CO2 that is good use Evalube oil.